Cerebral autoregulation is impaired in cardioinhibitory carotid sinus syndrome. Issue 6 (31st January 2006) - Parry, S W; Steen, N; Baptist, M; Fiaschi, K A; Parry, O; Kenny, R A
Abstract : Objectives: To compare changes in cerebral autoregulation in response to controlled, lower body negative pressure-induced hypotension in patients with carotid sinus syndrome (CSS) and case controls. Design: Prospective case controlled study. Setting: Secondary and tertiary referral falls and syncope service. Patients: 17 consecutive patients with CSS and 11 asymptomatic controls. Interventions: Hypotension insufficient to cause syncope induced by lower body negative pressure (minimum 30 mm Hg fall in systolic blood pressure (SBP)) during concomitant transcranial Doppler ultrasonography. Main outcome measures: Cerebral autoregulation (systolic, diastolic and mean middle cerebral arterial blood flow velocities and cerebrovascular resistance) with continuous end-tidal carbon dioxide and haemodynamic monitoring. Results: Cerebral autoregulatory indices differed significantly between patients with CSS and controls. Systolic, diastolic and middle cerebral arterial blood flow velocities were, respectively, 9.2 m/s (95% confidence interval (CI) 2.9 to 15.4 m/s), 4.7 m/s (95% CI 1.5 to 7.9 m/s) and 6.9 m/s (95% CI 2.5 to 11.4 m/s) slower in patients with CSS. Cerebrovascular resistance was significantly greater in patients with CSS than in controls at SBP nadir and suction release; differences were 0.9 mm Hg/m/s (95% CI 0.0 to 1.7 mm Hg/m/s) and 0.8 mm Hg/m/s (95% CI 0.0 to 1.7 mm Hg/m/s), respectively. End-tidal carbon dioxide and systemic haemodynamic variables were similar for patients and controls at baseline and during lower body negative pressure. Conclusions: Cerebral autoregulation is altered in patients with CSS. This difference may have aetiological implications in the differential presentation with falls and drop attacks rather than syncope.